POLICY Understanding the enablers and barriers to implementing smoke-free NHS sites across acute care trusts in Greater Manchester: results of a hospital staff survey. Issue 3 (2021) - Clegg, Hannah; Howle, Freya; Groom, Kathryn; Moore, Ryan; Hryhorskyj, Lynn; Grundy, Seamus; Tempowski, Alex; Turnpenny, Beth; Law, Hou; Sundar, Ram; Butt, Al-Tahoor; Abdelaziz, Muntasir; et al.
No abstract available